2020
DOI: 10.1177/1533033820936773
|View full text |Cite
|
Sign up to set email alerts
|

Elevated MYO10 Predicts Poor Prognosis and its Deletion Hampers Proliferation and Migration Potentials of Cells Through Rewiring PI3K/Akt Signaling in Cervical Cancer

Abstract: MYO10, recognized as an important regulator of cytoskeleton remodeling, has been reported to be associated with tumorigenesis. However, its functional implication in cervical cancer and potential mechanism still remain to be undetermined currently. MYO10 level in cervical cancer tissues was analyzed by using data retrieved from The Cancer Genome Atlas and ONCOMINE databases. Messenger RNA and protein expression levels were determined by quantitative real-time polymerase chain reaction and Western blot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 32 publications
(39 reference statements)
0
6
0
Order By: Relevance
“…Furthermore, studies on survivals revealed that patients with a high MYO10 expression had a worse chance to survive the disease overall. In addition, by rewiring the PI3K/Akt signaling pathway of CC caused by the knockdown or overexpression of MYO10, the capability of cervical cells in terms of proliferation, invasion, and migration was dramatically hindered or improved [ 31 ]. These findings showed that some tumor-related genes might have the potential to be employed as new biomarkers for the diagnosis and prognosis of individuals suffering from CC.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, studies on survivals revealed that patients with a high MYO10 expression had a worse chance to survive the disease overall. In addition, by rewiring the PI3K/Akt signaling pathway of CC caused by the knockdown or overexpression of MYO10, the capability of cervical cells in terms of proliferation, invasion, and migration was dramatically hindered or improved [ 31 ]. These findings showed that some tumor-related genes might have the potential to be employed as new biomarkers for the diagnosis and prognosis of individuals suffering from CC.…”
Section: Discussionmentioning
confidence: 99%
“…MYO10 is highly expressed in several types of cancer, and increased MYO10 promotes breast cancer invasion and metastasis 10,11 . Moreover, elevated MYO10 predicts poor prognosis and promotes cell proliferation and migration in cervical cancer 14 36 .…”
Section: Discussionmentioning
confidence: 99%
“… 10 , 11 Moreover, elevated MYO10 predicts poor prognosis and promotes cell proliferation and migration in cervical cancer. 14 Some researchers found that MYO10‐driven filopodia are crucial for leader driven NSCLC collective invasion. 36 Recently, it has been demonstrated that MYO10 drives genomic instability and inflammation in cancer.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, abnormalities in the fused eyelids and fingers, larynx and vagina are caused by failed programmed cell death [ 11 , 12 ]. The MYO10 gene plays a certain role in limb development and promotes cell migration in vivo and in vitro [ 13 , 14 ]. The six candidate genes obtained by second-generation sequencing in this study were analysed by Sanger sequencing and other methods.…”
Section: Discussionmentioning
confidence: 99%